The role of external customer mind-set among service employees. Issue 1 (9th February 2015) - Iyer, Rajesh; Johlke, Mark C
Abstract : Purpose: – The purpose of this study is to develop and test a model of the antecedents and outcomes of one aspect of customer mind-set (CMS) – external CMS (ECMS) — among front-line employees. The goal of this paper is to help managers address customer-level orientation by further investigating the external dimension of CMS (referred to as ECMS). Design/methodology/approach: – Data were gathered from a sample of front-line employees of a variety of firms located in a mid-sized southeastern US city. Findings: – The results indicate that greater amounts of job autonomy and job satisfaction are positively associated with front-line employee ECMS, while the employee's global role ambiguity, customer-specific ambiguity and role conflict are negatively associated with ECMS. In turn, front-line employee ECMS is associated with increased work motivation and sales performance. Research limitations/implications: – The data are cross-sectional in nature; so, strictly causal relations cannot be inferred from these results. Also, the sample primarily consists of younger females with less work experience and who are employed at smaller organizations. Therefore, future research should further test these relations in different samples to increase the robustness of the results. Practical implications: – This research utilizes a rich description of the front-line employee's job attitudes and work characteristics to build a model describing their association with the extent to which the ideas of market orientation have taken hold at the operational level and their relationship with the employee's motivation and subsequent performance. It shows that both internal and external characteristics are associated with front-line employee ECMS, which itself is very strongly related to desirable job outcomes. Originality/value: – The firm's financial performance is most directly affected by how well it serves its external customers. However, there has been no research on the role and the consequences of employee ECMS. There are only a few studies (less than five) that have empirically explored the CMS. Therefore, the many potential benefits from a deeper understanding of a market orientation culture and behaviors at the level of the front-line employee remain unclear, particularly in regards to its ECMS dimension.